The occurrence of hypertrophic pachymeningitis with infiltration of IgG4-positive plasma cells and with different aetiology: report of three cases. Issue 2 (3rd July 2017) - Ishikawa, Yuichi; Miyagawa, Ippei; Nakano, Kazuhisa; Satoh, Yurie; Todoroki, Yasuyuki; Kubo, Satoshi; Nawata, Aya; Nakayamada, Shingo; Saito, Kazuyoshi; Tanaka, Yoshiya
Abstract: We examined three patients with hypertrophic pachymeningitis (HP). The first patient was a 67-year-old man who underwent biopsy after being diagnosed with HP by magnetic resonance imaging (MRI) for loss of vision in the left eye. The patient's serum IgG4 level was 22.1 mg/dL and IgG4/IgG ratio in histopathological examination was approximately 30%, ruling out IgG4-related disease (IgG4-RD). The patient was subsequently diagnosed with Rosai–Dorfman disease after infiltration of S-100 protein-positive histiocytes was observed. The second patient was a 45-year-old man who underwent biopsy after being diagnosed with HP by MRI for eyelid swelling and double vision. The patient's serum IgG4 level was 42.8 mg/dL and IgG4/IgG ratio was approximately 25%, which ruled out IgG4-RD. The patient was subsequently diagnosed with idiopathic HP and idiopathic orbital pseudo-tumor. The third patient was a 66-year-old man who underwent biopsy after being diagnosed with HP by MRI for headache. The patient had an elevated serum IgG4 level of 771 mg/dL and a histopathologically determined IgG4/IgG ratio of 70% and was thus diagnosed with IgG4-RD. All the patients were treated with a glucocorticoid (prednisolone 0.6 mg/kg/day), and they responded well to the treatment. Although the clinical courses were very similar, HP was diagnosed differently in each patient. We report these three cases because we thought they are thought-provoking about the prediction of the treatment responsiveness and the potential need for a new disease classification system in HP, which is an intractable disease that is sometimes refractory to glucocorticoid therapy.